The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3989/mc.2014.04413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the strontium aluminate and hemihydrate contents on the properties of a calcium sulphoaluminate based cement

Abstract: ABSTRACT:The effect of strontium aluminate (SrAl 2 O 4 ) on the hydration process of a calcium sulphoaluminate (C 4 A 3 Ŝ ) cement was investigated. Cement pastes were prepared by mixing C 4 A 3 Ŝ , hemihydrate (CaSO 4 ·½H 2 O, CŜ H 0.5 ) and 0, 10 or 20wt% of SrAl 2 O 4 (SrA). The amount of CŜ H 0.5 was 15, 20 or 25wt% based on the C 4 A 3 Ŝ quantity. The cement pastes were hydrated using water to cement ratios (w/c) of 0.4 and 0.5. Samples were cured from 1 to 28 d. The compressive strength and setting time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(23 reference statements)
0
3
0
2
Order By: Relevance
“…Nano WMTA also consists of elements such as strontium salt and carbonate and zeolite, which are stabilizer agents (16, 17). Furthermore, scanning electron microscopic analysis of strontium aluminate in combination with gypsum showed that this component can reduce the size of ettringite, which in turn could decrease the void size between ettringite needlelike crystals (34). These findings are also consistent with previously published investigations (18, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Nano WMTA also consists of elements such as strontium salt and carbonate and zeolite, which are stabilizer agents (16, 17). Furthermore, scanning electron microscopic analysis of strontium aluminate in combination with gypsum showed that this component can reduce the size of ettringite, which in turn could decrease the void size between ettringite needlelike crystals (34). These findings are also consistent with previously published investigations (18, 20).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the generation of hydrogen gas under radiation, and the partial reaction of calcium sulphoaluminate particles with surrounding formed strontium aluminate. In these cement blocks ettringite is detected as smaller but needle shaped crystals; the presence of SrAl 2 O 4 inhibits the formation of ettringite crystals [33]. Also, as a result of carbonation, the cement blocks may undergo changes in the porosity of cement blocks.…”
Section: A-scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Carbonation of cement blocks results from the reactions of (C 3 S) and (C 2 S) with Carbon Dioxide. These reactions result in formation of CaCO 3 and silica gel, as follows [21,33]: There is a shift in the basal spacing of the cement. This can be attributed to the energy transferred from the gamma rays to the molecules of water and the cement components.…”
Section: A-scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…No obstante su empleo cada vez en crecimiento en las obras civiles ha demandado que se realicen estudios más detallados los cuales tienen como fin, entender el efecto de añadir el compuesto de aluminato de estroncio co-dopado con Eu,Dy (SrAl 2 O 4 :M, donde M=Eu 2+ , Dy 3+ .) en mezclas a base de Cemento Portland Ordinario (CPO) ( Velazco et al 2014) .…”
Section: Introductionunclassified
“…El artículo tiene como finalidad profundizar en el entendimiento del comportamiento físico y de las propiedades mecánicas de los compuestos cementantes fotoluminiscentes; así como también, analizar la influencia del SrAl 2 O 4 :M como parte de mezclas basadas en CPO a nivel macroscópico para su aplicación en la in-geniería civil. Se debe recalcar que el estudio a nivel físico-químico, atómico y molecular ha sido ya realizado en otras investigaciones anteriores (Ptáček et al, 2014;Velazco et al, 2014;Ptacek, 2014).…”
Section: Introductionunclassified